The emotional landscape of online teaching: An autoethnographic exploration of vulnerability and emotional reflexivity. (June 2022) - Song, Juyoung
Abstract: In this autoethnography, I share my lived experiences of emotions in online teaching. Employing the notion of vulnerability, I explore my feelings as I negotiated the specific structural conditions of online teaching and the challenges presented by social interactions, student participation, and by my own sense of my teacher-educator identity, mediated by my background as an Asian female, non-native English speaker. My reflection on my own sense of vulnerability brought to the forefront various dimensions of my personal and professional identity. I felt marginalized further in online teaching due to the lack of direct social interactions and my self-doubt about online pedagogy, which accentuates, rather than subdues, my status as a non-native speaker and deepens my emotional struggles in negotiating and reinventing my teacher identity. In stepping back and looking at my own sense of increasing vulnerability and at the same time re-living past experiences, I not only came to understand my own emotions, but also was able to develop sensitivity to students' emotions through a closer attention towards their silence and (non) participation. I end the autoethnography emphasizing the importance of emotional reflexivity in grappling with challenges in teaching, enabling both personal growth and professional transformation.